2011
DOI: 10.1097/hjh.0b013e328345d950
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial function affects early carotid atherosclerosis progression in hypertensive postmenopausal women

Abstract: In this prospective study we observed a significant interaction between baseline FMD, FMD change during follow-up and IMT progression in our population of hypertensive postmenopausal women. These results are in accordance with the suggestion that endothelial dysfunction is associated with enhanced atherosclerosis development. This hypothesis could provide a pathophysiological explanation for the increase in cardio-vascular and cerebro-vascular episodes recorded in hypertensive postmenopausal women with endothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…30 FMD is a measure of endothelial function, and impaired FMD, indicative of endothelial dysfunction, appears to link a variety of cardiovascular risk factors with the development 1213 and progression 3133 of atherosclerotic vascular disease. Impaired endothelial function is a systemic disease, and forearm endothelial dysfunction correlates with endothelial dysfunction in other vascular beds, including those of the heart.…”
Section: Discussionmentioning
confidence: 99%
“…30 FMD is a measure of endothelial function, and impaired FMD, indicative of endothelial dysfunction, appears to link a variety of cardiovascular risk factors with the development 1213 and progression 3133 of atherosclerotic vascular disease. Impaired endothelial function is a systemic disease, and forearm endothelial dysfunction correlates with endothelial dysfunction in other vascular beds, including those of the heart.…”
Section: Discussionmentioning
confidence: 99%
“…Cross-sectional studies have shown a correlation between FMD and C-IMT [61,62] and C- IMT progression over a 6-year follow- up in a population free of cardiovascular disease [63] or after 1 year, in hypertensive, postmenopausal women [64]. Impaired FMD has been shown to be an independent predictor of in-stent stenosis after single-vessel coronary interventions [65].…”
Section: Flow-mediated Dilationmentioning
confidence: 99%
“…Vascular abnormalities have been shown by some [5], but not all [6], to be associated with T2D-related cognitive compromise. A possible explanation for inconsistencies is that vascular abnormalities evolve, with functional typically preceding structural changes [7]. Nevertheless, research usually focuses on structural (primarily MRI), rather than functional assessments of vasculature.…”
Section: Introductionmentioning
confidence: 99%